Penerapan Wisata Ramah Lingkungan di Hutan Adat Imbo Putui Desa Petapahan Kecamatan Tapung Kabupaten Kampar - Defri Yoza; Pebriandi Pebriandi; Arya Arismaya Metananda; Sonia Somadona; Evi Sribudiani; Fifi Puspita (CANANG: Jurnal Pengabdian Masyarakat, 2023)
One of the tourist attractions that can support the regional economy in Kampar Regency is the imbo putui customary forest located in Petapahan Village, Tapung District, Kampar Regency. The location has a clean river with large trees around it. Many residents who come from Pekanbaru and other areas deliberately visit the imbo putui forest. The application of environmentally friendly tourism is carried out by observing the imbo putui customary forest area in accordance with environmentally friendly criteria. The development and tourist attraction of the imbo putui customary forest will have an impact on the arrival of visitors to the imbo putui customary forest tourist attraction, which will increase the income of the Petapahan Village community. The tourism sector is a potential sector to be developed as a source of regional income. The development of tourism depends on the visits that come to visit the place. The increase in the number of visits that occurs is a mirror of the continued development of tourism, to maintain and increase the number of tourist visits.